Estimation of inbreeding depression in Psidium guajava through seed attributes using S0, S1, and S2 families (Acta Scientiarum. Agronomy, 2025)
Inbreeding depression, resulting from self-pollination or mating between closely related plants, primarily impacts quantitative traits. This study aimed to assess inbreeding depression in guava seeds from two generations of self-pollination (S1 and S2) relative to open-pollinated (S0) seeds, focusing on seed physical and physiological attributes. Physical seed quality was assessed by determining the weight of 1,000 seeds and analyzing seed images using the GroundEye® instrument. Physiological quality was evaluated through germination and accelerated aging tests, along with the emergence speed index, root length, and shoot length. The results revealed no inbreeding depression in the first selfing generation. However, mild levels of inbreeding depression were observed across all traits in the second selfing generation. This study underscores the importance of understanding inbreeding depression dynamics in guava seeds, particularly in subsequent generations of self-pollination, for effective breeding and seed quality management.